1995
DOI: 10.1007/bf00298988
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound bone measurements: Normal values and comparison with bone mineral density by dual X-ray absorptiometry

Abstract: Normative data for qualitative ultrasound (QUS) measurements: speed of sound (SOS), broadband ultrasound attenuation (BUA), and stiffness were established in 118 healthy women aged 20-86 years and in 42 healthy men aged 22-76 years. The relations between age, weight, height, and QUS were studied. QUS measurements were negatively correlated with age in both sexes. In women, age was accepted as first factor (R2 = 0.39 for SOS, 0.35 for BUA, and 0.45 for stiffness, P < 0.001); weight was accepted as second factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 39 publications
6
41
0
Order By: Relevance
“…In our study, we examined whether gait speed predicts SOS values. Calcaneus measurements based on ultrasound and dual-energy X-ray absorptiometry (DXA) have been found to be useful tools for evaluating bone status [20,21]. The relationship between gait parameters and bone status has been examined using ultrasound parameters, and gait speed has been shown to be significantly associated with better bone quality in a cross-sectional study [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we examined whether gait speed predicts SOS values. Calcaneus measurements based on ultrasound and dual-energy X-ray absorptiometry (DXA) have been found to be useful tools for evaluating bone status [20,21]. The relationship between gait parameters and bone status has been examined using ultrasound parameters, and gait speed has been shown to be significantly associated with better bone quality in a cross-sectional study [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes have also been reported for water-coupled devices such as the Lunar Achilles. 17,18 Moris et al 18 found an annual decrease of 1.9 m/s for SOS and 0.59 dB/MHz for BUA using the Lunar Achilles device. Comparable decreases have been reported for Japanese and Chinese populations.…”
Section: Reference Databasementioning
confidence: 98%
“…However, there is little information about long term precision in vivo and only a few longitudinal studies on changes of QUS parameters over time have been published [48][49][50]. While precision expressed as percentage coefficient of variation (CV) looks excellent for velocity parameters [41, [46][47], this may be misleading because it does not take into account the range of values across subjects or if sensitivity to skeletal change [44][45][46]. In order to take into account these factors a standardised percentage coefficient of variation (SCV) should be defined.…”
Section: Conclusion Drawn From Current In Vivo Studies?mentioning
confidence: 99%